Khảo sát vai trò phòng hộ rủi ro của vàng với thị trường chứng khoán ASEAN6 - Trần Thị Tuấn, Anh; Ngô Thị Tường, Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This article focuses on examining the role of gold as a risk hedge and safe-haven asset in the ASEAN6 stock markets, including Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam. The results indicate that gold can be a weak risk hedge tool for the Philippines, Singapore, Thailand, and Vietnam, while serving as a strong safe-haven asset for Singapore, particularly in conditions of significant market volatility leading to negative returns. Gold is also considered a weak safe-haven asset in all other ASEAN6 countries. Quantile regression is employed to examine the role of gold at different quantiles of returns detail. In Indonesia and the Philippines, gold plays a risk hedge role only when gold prices are low. In Malaysia and Vietnam, gold can act as a risk hedge when gold returns are either very high or very low and as a safe-haven asset when gold returns increase significantly. In Singapore and Thailand, gold may function as a safe-haven asset when gold returns decrease to the lowest quantiles. The research results carry important management implications for investors, encouraging portfolio diversification and the use of information about the role of gold at different price levels to build market timing strategies.
Keywords: Risk-hedge asset; Safe-haven asset; Gold market; ASEAN6 stock markets; Quantile regression